EFFECT OF NANOSILICA ADDITIVE ON THE PERFORMANCE OF POLYMER MODIFIED ASPHALT BINDERS AND MIXTURES - BALA, NURA (2018)
Bitumen is essentially the main material for construction of flexible pavement. However, large increase in axle load and traffic volume together with harsh environmental conditions causes severe distresses such as rutting deformation and fatigue cracking on flexible pavements.